Feto-maternal outcome of pregnancy with thrombocytopenia - Kharadi, Kinjal K.; Shah, Sapana R.; Deliwala, Kruti J.; Parikh, Purvi M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Thrombocytopenia is the second most haematological abnormality in pregnancy where the platelets count below 1,50,000/µl. Gestational thrombocytopenia is most common cause of thrombocytopenia, accounts for 70% of thrombocytopenia in pregnancy. Methods: It is retrospective study with 30 antenatal women at any gestational age having thrombocytopenia, platelet count less than 1,50,000/µl at SVP Hospital, Ahmedabad during duration of May 2023-November 2023. All the pregnant women who attend OPD and admitted in SVP Hospital, Ahmedabad were included in the study. Results: The present study found that gestational thrombocytopenia (53.34%) accounted for most common cause of thrombocytopenia, followed by hypertensive disorders (10.0%), HELLP syndrome (6.67%), dengue and malaria (6.67%), DIC (6.67%) and ITP (3.34%) in which 53.34% women has mild, 36.67% has moderate and 10% has severe thrombocytopenia. In this study vaginal delivery accounts for 33.34% and caesarean delivery accounts for 66.67%. In present study 50.0% patient of gestational thrombocytopenia didn’t required any treatment. About 6.67% patients required transfusion of PRC and 33.34% of neonates needed NICU admission. Neonatal mortality due to complications like prematurity, septicemia was seen in 10.0% of the cases. Conclusions: Outcome of pregnancy with moderate to severe thrombocytopenia depends mainly on the etiology of thrombocytopenia. Early interdisciplinary evaluation of thrombocytopenia during pregnancy can help in optimizing care as fetal outcomes and management depend on the etiology.